Epidemiology of injuries in National Collegiate Athletic Association women's gymnastics: 2014-2015 through 2018-2019 - Chandran, A.; Roby, P. R.; Boltz, A. J.; Robison, H. J.; Morris, S. N.; Collins, C. L. (Journal of Athletic Training, 2021)
Context: Women's gymnastics athletes in the National Collegiate Athletic Association (NCAA) constitute a unique population of NCAA athletes given the nature and dynamics of the sport. Background: Routine examination of women's gymnastics injuries is important for identifying the evolving burden of injuries in this sport. Methods: Exposure and injury data collected in the NCAA Injury Surveillance Program during 2014-2015 through 2018-2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics; injury rate ratios were used to examine differential injury rates. Results: The overall injury rate was 8.00 per 1000 athlete-exposures; injury incidence was greater in competitions than in practices (injury rate ratio = 1.84; 95% CI = 1.48, 2.29), though practice injury rates increased during 2015-2016 through 2018-2019. Most injuries were classified as strains (16.5%), sprains (16.4%), and inflammatory conditions (12.3%), with overuse injuries prevalent among practice injuries (22.5%). Concussions (8.4%) were the most commonly reported specific injury. Summary: The increasing trend in practice injury incidence is noteworthy although competition injury rates were higher overall. Findings also suggest that the etiologies of overuse injuries and inflammatory conditions as well as the biomechanical aspects of concussions warrant further attention.